Bluetongue in Europe: past, present and future - Wilson, Anthony J. (The Royal Society, 2009)
The recent arrival in Northern and Western (NW) Europe of bluetongue virus (BTV), which causes the ruminant disease ‘bluetongue’, has raised the profile of this vector-borne ruminant disease and sparked discussions on the reasons for its sudden emergence so far north. This expansion has not happened in isolation and the disease has been expanding into Southern and Eastern Europe for the last decade. This shifting disease distribution is being facilitated by a number of different introduction mechanisms including the movement of infected livestock, the passive movement of infected Culicoides on the wind and, in NW Europe, an unknown route of introduction. The expansion of BTV in Europe has forced a re-evaluation of the importance of Palaearctic Culicoides species in transmission, as well as the importance of secondary transmission routes, such as transplacental transmission, in facilitating the persistence of the virus. The current European outbreak of BTV-8 is believed to have caused greater economic damage than any previous single-serotype outbreak. Although attempts are being made to improve the capacity of European countries to cope with future BTV incursions, the options available are limited by a lack of basic entomological data and limited virological surveillance.